The Concept of God's Ability (Qudratullah) in Islamic Education - Khambali, Khambali; Mahmud, Mahmud; Suhartini, Andewi (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
The purpose of this study is to describe the concept of qudratullah (the ability that Allah determines) or it can be said as destiny in relation to Islamic education based on explanations by commentators/ mufassirin and theologians in the study of kalam science, so as to straighten understanding of the concept of God's destiny. in the world of Islamic Education. This research is library research (library research) where the sources that are used as references in this research are taken from the library, such as books, books, articles, and others. This study also uses the maudhu'i interpretation method. The results of this study indicate that the verses that use the word Qadar describe the creation of the universe and everything in it and all its contents and all its provisions that apply to it is God's qadar through a just law, God also enforces it in the hereafter. All Muslims and schools of Islamic theology agree that Allah is God Almighty and Most Just in determining destiny and wills. However, when discussing the issues of free will (free will) and predestination (destiny, fatalism) they become the subject of very fierce debate among theologians. In Islamic education, the success of the educational process is not only determined by the human effort itself but is also determined by the X factor, namely biqudratillah.